Genetic diversity of currently circulating rubella viruses: a need to define more precise viral groups - Rivailler, P (J Gen Virol, 2017)
Recent studies have shown that the currently circulating rubella viruses are mostly members of two genotypes, 1E and 2B. Also, genetically distinct viruses of genotype 1G have been found in East and West Africa. This study used a Mantel test to objectively include both genetic diversity and geographic location in the definition of lineages, and identified statistically justified lineages (n=13) and sub-lineages (n=9) of viruses within genotypes 1G, 1E and 2B. Genotype 2B viruses were widely distributed, while viruses of genotype 1E as well as 1G and 1J were much more geographically restricted. This analysis showed that more precise groupings for rubella viruses are possible, which should improve the ability to track rubella viruses worldwide. A year-by-year analysis revealed gaps in surveillance that need to be resolved in order to support the surveillance needed for enhanced control and elimination goals for rubella.